Dimmable film and its usage method
Patent Information
- Application Number
- JP2025028923
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2026-09-07
AI Technical Summary
【0007】 本発明の実施形態によれば、駆動電圧が低減された調光フィルムが提供される。
Smart Images

Figure 2026142053000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a light control film and a method of using the same. [Background Art]
[0002] A light control film having a light control layer containing a composite material of a liquid crystal component and a polymer component between a pair of transparent electrode layers can change the scattering degree of transmitted light in accordance with the amount of voltage applied to the transparent electrode layers. For example, the light control film can switch between a light scattering state (scattering state) and a light transmitting state (transparent state) by switching whether voltage is applied to the transparent electrode layers (Patent Document 1). Utilizing such a function, application of the light control film to displays such as advertisements and information boards, smart windows and the like has been studied.
[0003] On the other hand, the light control film described above tends to have a higher driving voltage than general liquid crystal devices including a liquid crystal layer formed of a liquid crystal component. [Prior Art Documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Unexamined Patent Publication No. 2002-189123 [Summary of the Invention] [Problem to be Solved by the Invention]
[0005] A main object of the present invention is to provide a light control film with reduced driving voltage. [Means for Solving the Problem]
[0006] [1] According to one aspect of the present invention, a light-adjustable film is provided, having in this order a first transparent conductive film, a first light-adjustable layer, an intermediate layer, a second light-adjustable layer, and a second transparent conductive film, wherein the first light-adjustable layer and the second light-adjustable layer each contain a composite material of a liquid crystal component and a polymer component, and the intermediate layer contains an intermediate transparent electrode layer. [2] In the dimming film described in [1] above, the intermediate layer may further include a resin layer disposed on at least one side of the intermediate transparent electrode layer. [3] In the dimming film described in [2] above, the thickness of the resin layer may be 5 μm or less. [4] In the dimming film described in any of [1] to [3] above, the thickness of the intermediate layer may be 12 μm or less. [5] In the light-adjusting film described in any of [1] to [4] above, the sum of the thicknesses of the first light-adjusting layer and the second light-adjusting layer may be 5 μm or more. [6] In the light-adjusting film described in any of [1] to [5] above, the thickness of the first light-adjusting layer and the second light-adjusting layer may each be 50 μm or less. [7]According to another aspect of the present invention, a method of using the dimming film described in any of [1] to [6] above is provided. The method of use includes applying a voltage between the first transparent conductive film and the intermediate transparent electrode layer and between the second transparent conductive film and the intermediate transparent electrode layer. [Effects of the Invention]
[0007] According to an embodiment of the present invention, a dimmable film with reduced driving voltage is provided. [Brief explanation of the drawing]
[0008] [Figure 1] This is a schematic cross-sectional view showing the configuration of a light-adjusting film according to one embodiment of the present invention. [Figure 2A] This is a schematic diagram illustrating the relationship between the thickness of the dimming layer and the driving voltage in conventional dimming films. [Figure 2B]Figure 1 is a schematic diagram illustrating the relationship between the thickness of the dimming layer and the driving voltage in the dimming film shown. [Figure 3] This is a schematic cross-sectional view showing the configuration of a light-adjusting film according to one embodiment of the present invention. [Figure 4] This is a schematic cross-sectional view showing the configuration of a light-adjusting film according to one embodiment of the present invention. [Figure 5] This is a schematic diagram illustrating an example of a method for manufacturing a dimmable film according to one embodiment of the present invention. [Figure 6] This is a schematic diagram illustrating a dimming element according to one embodiment of the present invention. [Figure 7] This graph shows the relationship between the applied voltage and haze for the dimming films of the examples and comparative examples. [Figure 8] This graph shows the relationship between the applied voltage and total light transmittance of the dimming films in the examples and comparative examples. [Modes for carrying out the invention]
[0009] The embodiments of the present invention will be described below, but the present invention is not limited to these embodiments. Furthermore, each embodiment can be combined as appropriate. In order to clarify the explanation, the drawings may schematically represent the width, thickness, shape, etc. of each part compared to the embodiments, but these are merely examples and do not limit the interpretation of the present invention. In this specification, "~" representing a numerical range includes its upper and lower limits.
[0010] A. Dimmable film Figure 1 is a schematic cross-sectional view showing the configuration of a light-adjusting film according to one embodiment of the present invention. The light-adjusting film 100A has a first transparent conductive film 10, a first light-adjusting layer 20, an intermediate layer 30, a second light-adjusting layer 40, and a second transparent conductive film 50 in this order. These elements are preferably laminated in close contact with each other without an adhesive layer such as an adhesive layer or a tack layer.
[0011] The first transparent conductive film 10 includes a first transparent substrate 12 and a first transparent electrode layer 14 disposed on the side of the first light-adjusting layer 20. The second transparent conductive film 50 includes a second transparent substrate 52 and a second transparent electrode layer 54 disposed on the side of the second light-adjusting layer 40. The intermediate layer 30 is composed of an intermediate transparent electrode layer 34. The first light-adjusting layer 20 contains a composite material of a liquid crystal component 22 and a polymer component 24. Although not shown, the first light-adjusting layer 20 may further contain a dichroic dye depending on the purpose. When a voltage is applied to the first transparent electrode layer 14 and the intermediate transparent electrode layer 34, the liquid crystal component 22 is oriented in response to the electric field generated, which can change the degree of scattering of light transmitted through the first light-adjusting layer 20. The second light-adjusting layer 40 contains a composite material of a liquid crystal component 42 and a polymer component 44. Although not shown, the second light-adjusting layer 40 may further contain a dichroic dye depending on the purpose. When a voltage is applied to the intermediate transparent electrode layer 34 and the second transparent electrode layer 54, the liquid crystal component 42 is oriented according to the resulting electric field, which can change the degree of scattering of light transmitted through the second dimming layer 40.
[0012] As shown in Figure 2A, in a dimmable film 100A' in which a first transparent conductive film 10, a first dimmable layer 20, and a second transparent conductive film 50 are laminated in this order, the electric field strength (E) generated by applying voltage to the first transparent electrode layer 14 and the second transparent electrode layer 54 is expressed as E = V / d (V: voltage, d: thickness of the first dimmable layer). Therefore, if the thickness of the first dimmable layer is increased for purposes such as obtaining sufficient haze, the driving voltage required to drive the first dimmable layer will also increase. On the other hand, in dimmable film 100A, if the thickness of both the first dimmable layer 20 and the second dimmable layer 40 is halved (d / 2), the driving voltage can be halved while maintaining the total thickness of the dimmable layers included in the dimmable film. Specifically, as shown in Figure 2B, the electric field strength (E1) generated by applying voltage to the first transparent electrode layer 14 and the intermediate transparent electrode layer 34, and the electric field strength (E2) generated by applying voltage to the intermediate transparent electrode layer 34 and the second transparent electrode layer 54 are both 2V / d. Therefore, the voltage required to obtain the same electric field strength as the dimming film 100A' can be halved.
[0013] FIG. 3 is a schematic cross-sectional view showing the configuration of a light modulating film according to another embodiment of the present invention. The light modulating film 100B includes a first transparent conductive film 10, a first light modulating layer 20, an intermediate layer 30, a second light modulating layer 40, and a second transparent conductive film 50 in this order. The light modulating film 100B differs from the light modulating film 100A in that the intermediate layer 30 further includes a first resin layer 32 disposed on the first light modulating layer 20 side of the intermediate transparent electrode layer 34. Even in the configuration of the light modulating film 100B, if the thickness of the first resin layer 32 is small, the voltage drop caused by the thickness is suppressed, and the effects of the present invention can be obtained.
[0014] FIG. 4 is a schematic cross-sectional view showing the configuration of a light modulating film according to still another embodiment of the present invention. The light modulating film 100C includes a first transparent conductive film 10, a first light modulating layer 20, an intermediate layer 30, a second light modulating layer 40, and a second transparent conductive film 50 in this order. The light modulating film 100C differs from the light modulating film 100A in that the intermediate layer 30 further includes a first resin layer 32 disposed on the first light modulating layer 20 side of the intermediate transparent electrode layer 34 and a second resin layer 36 disposed on the second light modulating layer 40 side of the intermediate transparent electrode layer 34. Even in the configuration of the light modulating film 100C, if the thicknesses of the first resin layer 32 and the second resin layer 36 are small, voltage drops caused by these thicknesses are suppressed, and the effects of the present invention can be obtained.
[0015] The driving voltage of the light modulating film according to an embodiment of the present invention is, for example, 100 V or less, preferably 5 V to 80 V, and more preferably 10 V to 60 V. Here, the driving voltage of the light modulating film means a voltage that, when applied to each electrode layer of the light modulating film, enables switching from a scattering state to a transparent state or from a transparent state to a scattering state. In the present specification, the term "voltage-applied state" may refer to a state in which a driving voltage is applied to each electrode layer.
[0016] The haze of the light modulating film in the scattering state is, for example, 80% or more, and preferably 90% to 100%. The haze of the light modulating film in the transparent state is lower than the haze of the light modulating film in the scattering state. The haze of the light modulating film in the transparent state is, for example, 20% or less, and preferably 0% to 10%.
[0017] When the first light-modulating layer and / or the second light-modulating layer contains a dichroic dye, the total light transmittance of the light-modulating film in a scattering state is, for example, 0.01% to 10%, and may preferably be 0.01% to 5%. When the first light-modulating layer and the second light-modulating layer do not contain a dichroic dye, the above total light transmittance is, for example, 40% to 90%, and may preferably be 50% to 90%.
[0018] The total light transmittance of the light-modulating film in a transparent state may be not less than the total light transmittance of the light-modulating film in a scattering state. When the first light-modulating layer and / or the second light-modulating layer contains a dichroic dye, the total light transmittance of the light-modulating film in a transparent state is, for example, 10% to 70%, and may preferably be 20% to 70%. When the first light-modulating layer and the second light-modulating layer do not contain a dichroic dye, the above total light transmittance is, for example, 70% to 95%, and may preferably be 80% to 95%.
[0019] The thickness of the above-mentioned light-modulating film is, for example, 50 μm to 500 μm, may preferably be 80 μm to 400 μm, and more preferably be 100 μm to 300 μm.
[0020] <First Transparent Conductive Film and Second Transparent Conductive Film> The first transparent conductive film 10 and the second transparent conductive film 50 each include a first transparent substrate 12 and a second transparent substrate 52, as well as a first transparent electrode layer 14 and a second transparent electrode layer 54 disposed on one side thereof. Depending on the driving mode, alignment films may be provided on the surfaces of the first transparent electrode layer and the second transparent electrode layer. The first transparent conductive film and the second transparent conductive film may have the same configuration or different configurations. In other words, the first transparent substrate and the second transparent substrate may be the same substrate or different substrates. Also, the first transparent electrode layer and the second transparent electrode layer may be the same electrode layer or different electrode layers. Hereinafter, "first transparent conductive film and second transparent conductive film," "first transparent substrate and second transparent substrate," and "first transparent electrode layer and second transparent electrode layer" will be collectively described as "transparent conductive film," "transparent substrate," and "transparent electrode layer," respectively.
[0021] The surface resistance of the transparent conductive film (more specifically, the surface resistance of the transparent electrode layer) is preferably 1Ω / □ to 1000Ω / □, more preferably 5Ω / □ to 300Ω / □, and even more preferably 10Ω / □ to 200Ω / □.
[0022] The haze of the transparent conductive film is preferably 20% or less, more preferably 10% or less, and even more preferably 0.1% to 10%.
[0023] The total light transmittance of the transparent conductive film is preferably 40% or more, more preferably 60% or more, and even more preferably 80% or more.
[0024] Transparent substrates can be formed using any suitable material. Typically, transparent substrates are polymer films mainly composed of thermoplastic resins. Examples of thermoplastic resins include polyester resins such as polyethylene terephthalate (PET); cycloolefin resins such as polynorbornene; acrylic resins; polycarbonate resins; and cellulose resins. Among these, polyester resins, cycloolefin resins, or acrylic resins are preferred. These resins exhibit excellent transparency, mechanical strength, thermal stability, and moisture shielding properties. The above thermoplastic resins may be used individually or in combination of two or more types.
[0025] The thickness of the transparent substrate is preferably 10 μm to 200 μm, more preferably 15 μm to 100 μm, and even more preferably 20 μm to 70 μm, from the viewpoint of its function as a support for the light-adjusting layer and ease of handling.
[0026] The total light transmittance of the transparent substrate is preferably 40% or more, more preferably 60% or more, and even more preferably 80% or more.
[0027] The transparent electrode layer can be formed using metal oxides such as indium oxide, tin oxide, zinc oxide, indium-tin composite oxide (ITO), tin-antimony composite oxide, zinc-aluminum composite oxide, or indium-zinc composite oxide. In this case, the metal oxide may be an amorphous metal oxide or a crystalline metal oxide. Alternatively, the transparent electrode layer can be formed using metal nanowires such as silver nanowires (AgNW), carbon nanotubes (CNTs), organic conductive films, metal layers, or laminates thereof. Preferably, a transparent electrode layer containing ITO is formed. A transparent electrode layer containing ITO has excellent transparency. The transparent electrode layer can be patterned into a desired shape depending on the purpose.
[0028] The total light transmittance of the transparent electrode layer is preferably 85% or higher, more preferably 87% or higher, and even more preferably 90% or higher. By using a transparent electrode layer having a total light transmittance within this range, a light-adjusting film with high total light transmittance in the transparent state can be obtained. The higher the total light transmittance, the better, and its upper limit is, for example, 99%.
[0029] The thickness of the transparent electrode layer can be appropriately set according to the desired properties, forming material, etc. The thickness of the transparent electrode layer formed by a metal oxide is, for example, 10 nm or more, preferably 15 nm or more, and also, for example, 50 nm or less, preferably 35 nm or less, and more preferably 30 nm or less. The thickness of the transparent electrode layer formed by silver nanowires is, for example, 10 nm or more, preferably 20 nm or more, and also, for example, 1000 nm or less, preferably 500 nm or less.
[0030] A transparent conductive film can be obtained by forming a transparent electrode layer on one side of a transparent substrate using any suitable film formation method, such as sputtering, vacuum deposition, CVD, ion plating, spraying, or coating. After forming the metal oxide layer, a transparent electrode layer made of crystalline metal oxide can be obtained by annealing. Annealing is performed, for example, by heat treatment at 120°C to 300°C for 10 to 120 minutes.
[0031] <First and second dimming layers> The first dimming layer 20 and the second dimming layer 40 each contain a composite material of liquid crystal components 22 and 42 and polymer components 24 and 44. The first dimming layer and the second dimming layer may have the same configuration or different configurations. Hereinafter, the "first dimming layer and the second dimming layer" will be described collectively as the "dimming layer".
[0032] The above-described light-modulating layer may have a structure in which liquid crystal components are held as droplets or a continuous phase within a polymer component. When a voltage is applied to a pair of transparent electrode layers sandwiching such a light-modulating layer, the liquid crystal components may orient according to the direction of the electric field, resulting in a change in the degree of scattering of light transmitted through the light-modulating layer.
[0033] In one embodiment, the light-adjusting layer becomes transparent when a voltage is applied and scatters when no voltage is applied (normal mode). In this embodiment, when no voltage is applied, the liquid crystal components are not oriented, resulting in a scattering state due to the difference in refractive index between the polymer component and the liquid crystal component. When a voltage is applied, the liquid crystal components become oriented, and as a result of the refractive index of the liquid crystal components becoming the same as that of the polymer component, the layer becomes transparent.
[0034] In another embodiment, the dimming layer enters a scattering state when a voltage is applied and becomes transparent when no voltage is applied (reverse mode). In this embodiment, the alignment film provided on the surface of the transparent electrode layer causes the liquid crystal components to align in a predetermined direction when no voltage is applied, resulting in the liquid crystal components and polymer components matching in refractive index, thus becoming transparent. When a voltage is applied, the orientation of the liquid crystal components changes, resulting in a scattering state.
[0035] Examples of the above-mentioned dimming layers include dimming layers containing polymer-dispersed liquid crystals (hereinafter also referred to as "PDLC layers") and dimming layers containing polymer-network liquid crystals (hereinafter also referred to as "PNLC layers"). The dimming layers 20 and 40 shown in Figures 1 to 4 are normal-mode PDLC layers and have a structure in which liquid crystal droplets 26 and 46 containing liquid crystal components 22 and 42 are dispersed in polymer matrices (polymer components) 24 and 44. PNLC has a structure in which liquid crystal components are held in spaces within a polymer network (polymer component), and the spaces in which the liquid crystal components are held (hereinafter also referred to as "liquid crystal domains") may have a continuous phase.
[0036] In PDLC, the average particle size of the liquid crystal droplets may be, for example, 0.05 μm to 9 μm, preferably 0.1 μm to 8 μm. The average particle size of the liquid crystal droplets is the volume-average particle size of the liquid crystal droplets when viewed from a direction perpendicular to the main surface of the light-adjusting film. In PNLC, the average diameter of the liquid crystal domains may be, for example, 0.05 μm to 9 μm, preferably 0.1 μm to 8 μm.
[0037] The polymer matrix or polymer network may be composed of any suitable polymer components. The polymer components may be formed from thermoplastic resins or curable resins. These resins may be appropriately selected depending on the light transmittance, refractive index of the liquid crystal component, adhesion to the transparent conductive film, etc. As thermoplastic resins, water-soluble or water-dispersible resins such as urethane resins, polyvinyl alcohol resins, polyethylene resins, polypropylene resins, and acrylic resins are preferably used. Examples of curable resins include polymerizable liquid crystal components, (meth)acrylic resins, silicone resins, epoxy resins, fluororesins, polyester resins, and polyimide resins. The polymer components may be used individually or in combination. The difference between the refractive index of the polymer component and the ordinary or extraordinary refractive index of the liquid crystal component may be, for example, 0.0 to 0.05.
[0038] As the liquid crystal component, any suitable liquid crystal compound can be used alone or in combination of two or more, depending on the birefringence, refractive index of the polymer component, etc. The dielectric anisotropy of the liquid crystal component may be positive or negative. The liquid crystal component may be, for example, a nematic, smectic, or cholesteric liquid crystal component. It is preferable to use a nematic liquid crystal component because it can achieve high transparency in the oriented state. Note that the properties of the liquid crystal component (birefringence, dielectric constant, etc.) refer to the properties of the liquid crystal component as a whole, which may contain two or more liquid crystal compounds.
[0039] Examples of nematic liquid crystal compounds include biphenyl compounds, phenylbenzoate compounds, cyclohexylbenzene compounds, azoxybenzene compounds, azobenzene compounds, azomethine compounds, terphenyl compounds, biphenylbenzoate compounds, cyclohexylbiphenyl compounds, phenylpyridine compounds, cyclohexylpyrimidine compounds, cholesterol compounds, and fluorine compounds. These liquid crystal compounds may be used individually or in combination.
[0040] The birefringence Δn of the liquid crystal component at a wavelength of 589 nm is preferably 0.05 to 0.50, and more preferably 0.10 to 0.45.
[0041] The content of polymer components in the light-adjusting layer is, for example, 30% to 70% by weight, preferably 35% to 65% by weight, and more preferably 40% to 60% by weight. If the content of polymer components is within this range, effects such as good mechanical strength and prevention of liquid crystal leakage from the edges can be obtained.
[0042] The liquid crystal component content in the light-adjusting layer is, for example, 30% to 70% by weight, preferably 35% to 65% by weight, and more preferably 40% to 60% by weight.
[0043] The weight ratio of polymer components to liquid crystal components in the light-adjusting layer (former:latter) is, for example, 30:70 to 70:30, preferably 35:65 to 65:35, and more preferably 40:60 to 60:40.
[0044] The total content ratio of polymer components and liquid crystal components in the light-adjusting layer may be, for example, 80% by weight or more, preferably 90% to 99.9% by weight, and preferably 95% to 99.9% by weight.
[0045] The light-adjusting layer may contain any appropriate additive components depending on the purpose. Examples of additive components include dichroic dyes, surfactants (dispersants), leveling agents, and crosslinking agents.
[0046] When the light-adjusting layer contains a dichroic dye, the dichroic dye can be oriented along the liquid crystal components. Therefore, in the scattering state, the light-adjusting layer containing the dichroic dye exhibits absorption (in other words, coloring) due to the dichroic dye, and can exhibit shielding and design properties due to the above-mentioned coloring, while in the transparent state, it may exhibit lower absorption and haze than in the scattering state. From the viewpoint of obtaining high transmittance in the transparent state, it is preferable that the dichroic dye exists in the liquid crystal droplets or liquid crystal domains in the light-adjusting layer.
[0047] As the dichroic dye, any suitable dichroic dye can be used that has absorption in a desired wavelength range (e.g., a desired maximum absorption wavelength) and is compatible with the liquid crystal component. The dichroic dye may have a positive or negative Δε. The dichroic dye itself may also exhibit liquid crystal properties. Only one type of dichroic dye may be used, or two or more types may be used in combination.
[0048] Specific examples of dichroic dyes include azo dyes, anthraquinone dyes, naphthoquinone dyes, perylene dyes, quinophthalone dyes, tetrazine dyes, and benzothiadiazole dyes. Among these, from the viewpoint of absorption coefficient, solubility in liquid crystal components, and lightfastness, it is preferable that the dichroic dye contains anthraquinone dyes or azo dyes. For example, azo dyes, anthraquinone dyes, or mixtures thereof described on pages 192-196 and 724-730 of "Liquid Crystal Device Handbook" edited by the 142nd Committee of the Japan Society for the Promotion of Science, published by Nippon Kogyo Shinbunsha (1989) can be used. In addition, various dichroic dyes are commercially available and can be used as appropriate.
[0049] The content of the dichroic dye is, for example, 0.1 to 10 parts by weight, preferably 1 to 10 parts by weight, and more preferably 3 to 10 parts by weight, per 100 parts by weight of the liquid crystal component. The total content of additive components other than the dichroic dye in the light-adjusting layer is, for example, 0.5% to 20% by weight, and preferably 1% to 10% by weight.
[0050] The thickness of the first dimming layer and the second dimming layer are, independently of each other, for example, 50 μm or less, preferably 2 μm to 40 μm, and more preferably 4 μm to 30 μm. In particular, when the thickness of the first dimming layer and the second dimming layer are 20 μm or less or 10 μm or less, a suitable reduction in driving voltage can be obtained.
[0051] The combined thickness of the first and second photochromic layers is, for example, 100 μm or less, preferably 4 μm to 80 μm, and more preferably 8 μm to 60 μm. In particular, when the combined thickness of the first and second photochromic layers is 5 μm or more or 10 μm or more, high haze or coloration can be suitably obtained in the scattering state.
[0052] The light-adjusting layer can be fabricated by any suitable method. For example, emulsion-based and polymerization-induced phase separation methods can be used to fabricate the PDLC layer.
[0053] A method for producing an emulsion-type PDLC layer includes, for example, applying an emulsion coating solution containing a polymer matrix-forming resin (typically a thermoplastic resin) and a liquid crystal component to the transparent electrode layer surface of a transparent conductive film to form a coating layer, and drying the coating layer to form a polymer matrix in the polymer matrix-forming resin. The emulsion coating solution is preferably an emulsion containing a liquid crystal component as a dispersed phase. The emulsion coating solution may be, for example, an emulsion in which liquid crystal particles containing a liquid crystal component and polymer matrix-forming resin particles are dispersed in a dispersion medium such as water, an aqueous organic solvent, or a mixture thereof. By applying and drying the emulsion coating solution, a PDLC layer having a structure in which liquid crystal droplets are dispersed in a polymer matrix can be formed.
[0054] In the above emulsion method, a liquid crystal emulsion containing liquid crystal particles whose particle size and particle size distribution have been controlled in advance by a membrane emulsification method or the like can be prepared, and the emulsion coating solution can be prepared by mixing the liquid crystal emulsion with a polymer matrix-forming resin dispersion. By using a liquid crystal emulsion in which the particle size and particle size distribution of the liquid crystal particles have been standardized in advance, a PDLC layer containing liquid crystal droplets with a desired particle size and particle size distribution can be suitably obtained. Furthermore, if the light-adjusting layer contains a dichroic dye, a liquid crystal emulsion containing liquid crystal components and a dichroic dye can be prepared, and by dispersing the liquid crystal particles in a polymer matrix-forming resin, the dissolution of the dichroic dye into the polymer matrix can be prevented, and a PDLC layer with a high dichroic ratio can be obtained.
[0055] A method for producing a PDLC layer using polymerization-induced phase separation includes, for example, applying a coating solution containing an active energy ray-curable resin and a liquid crystal component to the transparent electrode layer surface of a transparent conductive film to form a coating layer, laminating an intermediate layer on the coating layer to form a laminate, and irradiating the laminate with active energy rays to cure (polymerize) the curable resin and separate the polymer matrix from the liquid crystal component. The coating solution is preferably a homogeneous phase. Alternatively, the coating solution may be filled between the laminated transparent conductive film and the intermediate layer via a spacer, and then phase separation may be performed by irradiation with active energy rays.
[0056] <Middle class> The intermediate layer 30 includes an intermediate transparent electrode layer 34. The intermediate layer may further include a resin layer disposed on one or both sides of the intermediate transparent electrode layer, as needed. Depending on the driving mode, an alignment film may also be provided on the light-modulating layer side surface of the intermediate layer. To drive one light-modulating layer, a pair of electrode layers arranged to sandwich the light-modulating layer are required. In the light-modulating film according to the embodiment of the present invention, the intermediate transparent electrode layer serves as both the electrode layer for driving the first light-modulating layer and the electrode layer for driving the second light-modulating layer. In other words, according to the light-modulating film according to the embodiment of the present invention, two light-modulating layers arranged alternately between them can be driven using three transparent electrode layers.
[0057] The same explanation as for the first and second transparent electrode layers can be applied to the intermediate transparent electrode layer.
[0058] The resin layer can support and protect the intermediate transparent electrode layer. By placing the resin layer on at least one side of the intermediate transparent electrode layer, cracking of the transparent electrode layer can be prevented and the handling of the intermediate layer can be improved. Furthermore, corrosion of the intermediate transparent electrode layer can be suppressed. For example, by providing resin layers on both sides of a transparent electrode layer formed of silver nanowires, corrosion of the transparent electrode layer can be suitably suppressed.
[0059] The 50nm depth hardness of the resin layer obtained by nanoindentation is preferably 0.3 GPa or higher, more preferably 0.32 GPa or higher, and even more preferably 0.4 GPa or higher. The upper limit of the 50nm depth hardness of the resin layer obtained by nanoindentation is preferably 5 GPa or lower, and more preferably 2 GPa or lower. The "50nm depth hardness by nanoindentation" is determined by continuously measuring the load applied to the indenter and the indentation depth during loading and unloading when an indenter is pressed into the surface of the resin layer, and obtaining the load-indentation depth curve. In this specification, the conditions for this measurement are: evaluation temperature: 25°C, loading / unloading speed: 1000 nm / s, and indentation depth: 50 nm. The "50nm depth hardness H by nanoindentation" is calculated from the load when indented to 50 nm (maximum load Pmax) and the contact area between the indenter and the sample (contact projected area Ac) using the formula: H = Pmax / Ac. The hardness described above can be controlled by the type of resin constituting the resin layer, the type and composition of the monomer components constituting the resin, the degree of polymerization, and so on.
[0060] The resin layer is typically a cured or solidified layer of a resin. The cured layer may be, for example, a cured layer of a thermosetting resin or an active energy ray curable resin. The solidified layer may be, for example, a solidified layer of a coated film of a thermoplastic resin solution. Preferably, the resin layer is a cured layer of a curable resin. Examples of curable resins constituting the resin layer include acrylic resins, epoxy resins, silicone resins, urethane resins, or mixtures thereof. Examples of thermoplastic resins constituting the resin layer include acrylic resins, epoxy resins, polyester resins, and urethane resins, or mixtures thereof.
[0061] The glass transition temperature of the resin constituting the resin layer is preferably 120°C to 300°C, and more preferably 130°C to 250°C.
[0062] The cured resin layer can be formed, for example, by applying a resin layer-forming composition onto a temporary support and then curing the composition.
[0063] The resin layer forming composition preferably includes, as a main curable compound, a polyfunctional monomer, an oligomer derived from a polyfunctional monomer, and / or a prepolymer derived from a polyfunctional monomer. Examples of polyfunctional monomers include tricyclodecanedimethanol diacrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane triacrylate, pentaerythritol tetra(meth)acrylate, dimethylolpropane tetraacrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol(meth)acrylate, 1,9-nonanediol diacrylate, 1,10-decanediol(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, dipropylene glycol diacrylate, isocyanuric acid tri(meth)acrylate, ethoxylated glycerin triacrylate, and ethoxylated pentaerythritol tetraacrylate. Polyfunctional monomers may be used individually or in combination.
[0064] The content ratio of the above-mentioned polyfunctional monomer, oligomer derived from polyfunctional monomer, and prepolymer derived from polyfunctional monomer is preferably 30% to 100% by weight, more preferably 40% to 95% by weight, and particularly preferably 50% to 95% by weight, based on the total amount of monomer, oligomer, and prepolymer in the resin layer forming composition.
[0065] The above resin layer-forming composition may contain a monofunctional monomer. When the above resin layer-forming composition contains a monofunctional monomer, the content of the monofunctional monomer is preferably 40% by weight or less, and more preferably 20% by weight or less, relative to the total amount of monomers, oligomers, and prepolymers in the resin layer-forming composition.
[0066] Examples of the above monofunctional monomers include ethoxylated o-phenylphenol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, 2-ethylhexyl acrylate, lauryl acrylate, isooctyl acrylate, isostearyl acrylate, cyclohexyl acrylate, isoflonyl acrylate, benzyl acrylate, 2-hydroxy-3-phenoxyacrylate, acryloylmorpholine, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and hydroxyethylacrylamide.
[0067] The resin layer-forming composition may contain urethane (meth)acrylate and / or urethane (meth)acrylate oligomers. The urethane (meth)acrylate can be obtained, for example, by reacting hydroxy(meth)acrylate obtained from (meth)acrylic acid or (meth)acrylic acid ester and a polyol with a diisocyanate. The urethane (meth)acrylate and urethane (meth)acrylate oligomers may be used alone or in combination.
[0068] Examples of the above-mentioned (meth)acrylic acid esters include methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, and cyclohexyl (meth)acrylate.
[0069] Examples of the polyols mentioned above include ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, diethylene glycol, dipropylene glycol, neopentyl glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, 1,9-nonanediol, 1,10-decanediol, 2,2,4-trimethyl-1,3-pentanediol, 3-methyl-1,5-pentanediol, neopentyl glycol ester of hydroxypivalate, tricyclodecanedimethylol, 1,4-cyclohexanediol, spiroglycol, tricyclodecanedimethylol, hydrogenated bisphenol A, ethylene oxide-added bisphenol A, propylene oxide-added bisphenol A, trimethylolethane, trimethylolpropane, glycerin, 3-methylpentane-1,3,5-triol, pentaerythritol, dipentaerythritol, tripentaerythritol, glucose, and the like.
[0070] As the above-mentioned diisocyanate, for example, various aromatic, aliphatic, or alicyclic diisocyanates can be used. Specific examples of the above-mentioned diisocyanate include tetramethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 2,4-tole diisocyanate, 4,4-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 3,3-dimethyl-4,4-diphenyl diisocyanate, xylene diisocyanate, trimethylhexamethylene diisocyanate, 4,4-diphenylmethane diisocyanate, and their hydrogenated products.
[0071] The total content of the above-mentioned urethane (meth)acrylate and urethane (meth)acrylate oligomer is, for example, 5% to 100% by weight, and can be 5% to 70%, 5% to 50%, or 5% to 30% by weight, relative to the total amount of monomers, oligomers, and prepolymers in the resin layer-forming composition. Within this range, a resin layer with an excellent balance of hardness, flexibility, and adhesion can be formed.
[0072] The resin layer forming composition preferably contains any suitable photopolymerization initiator. The resin layer forming composition may further contain a solvent and desired additives. Examples of additives include leveling agents, antiblocking agents, dispersion stabilizers, thixotropes, antioxidants, UV absorbers, defoaming agents, thickeners, dispersants, surfactants, catalysts, fillers, lubricants, and antistatic agents. Furthermore, by incorporating conductive fine particles, electrical connection between the resin layer and the intermediate transparent electrode layer can be ensured.
[0073] Any suitable curing treatment can be used as the curing method for the resin layer forming composition. Typically, the curing treatment is performed by ultraviolet irradiation. The cumulative amount of ultraviolet irradiation is preferably 200 mJ to 400 mJ. Before curing the resin layer forming composition, the coating layer formed by the resin layer forming composition may be heated. The heating temperature is preferably 60°C to 140°C, more preferably 70°C to 130°C, and even more preferably 80°C to 120°C.
[0074] The solidified resin layer can be formed, for example, by applying a resin solution obtained by dissolving or dispersing a thermoplastic resin in an aqueous solvent or organic solvent onto a temporary support, and then drying and solidifying the coated film. The resin concentration in the resin solution is, for example, 3 to 20 parts by weight per 100 parts by weight of solvent. The drying temperature and drying time can be appropriately set depending on the type of resin, the concentration of the resin solution, the thickness of the coated layer, etc. The drying temperature is, for example, 100°C or less, preferably 50°C to 70°C. The drying time may be, for example, 1 to 10 minutes.
[0075] The thickness of the resin layer is, for example, 5 μm or less, preferably 0.1 μm to 4 μm, and more preferably 0.2 μm to 3 μm. If the thickness of the resin layer exceeds the above upper limit, a voltage drop may occur due to the thickness of the resin layer when driving the photochromic layer (for example, the first photochromic layer 20 in Figure 3) in which the resin layer is placed between the intermediate transparent electrode layer. If the thickness of the resin layer is less than the above lower limit, the function of the resin layer may not be fully exhibited, or it may become difficult to form the resin layer.
[0076] Preferably, a resin film is used as the temporary support. Examples of resins that make up the resin film include cycloolefin resins, polyimide resins, polyvinylidene chloride resins, polyvinyl chloride resins, polyethylene terephthalate resins, polyethylene naphthalate resins, and the like.
[0077] If necessary, various surface treatments can be applied to the resin film. For example, the side of the resin film on which the resin layer is formed may be treated with a release agent such as a silicone-based, fluorine-based, long-chain alkyl-based, or fatty acid amide-based release agent. By using the resin film treated with the release agent as a temporary support, the transfer of the intermediate layer can be suitably performed.
[0078] The thickness of the temporary support is preferably 8 μm to 500 μm, and more preferably 50 μm to 250 μm.
[0079] An intermediate layer can be obtained by forming an intermediate transparent electrode layer on the surface of a resin layer formed on a temporary support, thereby including the intermediate transparent electrode layer and a resin layer disposed on one side thereof. For specific embodiments of such an intermediate layer, see, for example, Japanese Patent Application Publication No. 2019-031041. Alternatively, an intermediate layer can be formed on a temporary support by forming another resin layer on the surface of the intermediate transparent electrode layer of a laminate having the configuration of [temporary support / resin layer / intermediate transparent electrode layer] in the same manner as described above, thereby including the intermediate transparent electrode layer and resin layers disposed on both sides thereof. In this case, the two resin layers disposed on both sides of the intermediate transparent electrode layer may have the same configuration (forming material, physical properties, thickness, etc.) or may have different configurations. Furthermore, the intermediate transparent electrode layer may be formed directly on the temporary support. This can result in an intermediate layer composed of the intermediate transparent electrode layer. The intermediate layer formed on the temporary support can be transferred to a first or second photochromic layer to constitute a photochromic film.
[0080] The thickness of the intermediate layer is preferably 12 μm or less, more preferably 0.1 μm to 10 μm or less, and may be, for example, 0.2 μm or more, 0.3 μm or more, 0.4 μm or more, or 0.5 μm or more, and may be, for example, 5 μm or less, 4 μm or less, or 3 μm or less.
[0081] B. Method for manufacturing dimmable film The light-adjustable film described in Section A can be manufactured by any suitable manufacturing method. Figure 5 is a schematic diagram illustrating an example of a manufacturing method for the light-adjustable film 100B. As shown in Figures 5(a) and 5(e), first, the second transparent conductive film 50 and the first transparent conductive film 10 are prepared. Next, as shown in Figures 5(b) and 5(f), an emulsion coating solution is applied and dried on the second transparent electrode layer 54 of the second transparent conductive film 50 and the first transparent electrode layer 14 of the first transparent conductive film 10 to form the second light-adjustable layer (second PDLC layer) 40 and the first light-adjustable layer (first PDLC layer) 20. Next, as shown in Figure 5(c), a laminated film 39 of a temporary support 38, a first resin layer 32, and an intermediate transparent electrode layer 34 is laminated on the second light-adjustable layer 40 such that the intermediate transparent electrode layer 34 is in close contact with the second light-adjustable layer 40. Next, as shown in Figure 5(d), the temporary support 38 is peeled off. This yields a laminate 60 on which an intermediate layer 30, including an intermediate transparent electrode layer 34 and a first resin layer 32, is transferred onto the second light-adjusting layer 40. Next, as shown in Figure 5(g), the laminate 60 is laminated on the first light-adjusting layer 20 such that the first resin layer 32 is in close contact with the first light-adjusting layer 20. This yields a light-adjusting film 100B having the configuration of [first transparent substrate 12 / first transparent electrode layer 14 / first light-adjusting layer 20 / first resin layer 32 / intermediate transparent electrode layer 34 / second light-adjusting layer 40 / second transparent electrode layer 54 / second transparent substrate 52]. Preferably, as shown in Figure 5(h), the ends of the first transparent electrode layer 14, the second transparent electrode layer 54, and the intermediate transparent electrode layer 34 can be exposed by half-cutting or the like, and power supply electrodes 71, 72, and 73 can be provided on the exposed portions. The exposure of the first transparent electrode layer 14 may be achieved by offsetting the two layers during lamination as shown in Figure 5(g) and removing the first light-adjusting layer 20. Wiring can be connected to the power supply electrode to supply power from the power supply circuit.
[0082] C. How to use dimmable film The method of using the dimming film described in Section A typically involves applying a voltage between the first transparent conductive film and the intermediate transparent electrode layer, and between the second transparent conductive film and the intermediate transparent electrode layer. Depending on the desired transmittance and / or haze, the amount of voltage applied to the first transparent conductive film and the intermediate transparent electrode layer, and the amount of voltage applied to the second transparent conductive film and the intermediate transparent electrode layer, can be adjusted. For example, a predetermined voltage may be applied and / or the applied voltage may be set to zero.
[0083] Figure 6 is a schematic diagram illustrating a dimming element including the dimming film described above. The dimming element 200 includes a dimming film 100B, a first transparent conductive film 10 (specifically, a first transparent electrode layer 14), a second transparent conductive film 50 (specifically, a second transparent electrode layer 54), and a power supply circuit 220 that applies a driving voltage to the intermediate transparent electrode layer 34. The power supply circuit 220 applies a voltage between the first transparent conductive film 10 and the intermediate transparent electrode layer 34, and between the second transparent conductive film 50 and the intermediate transparent electrode layer 34. With the above configuration, a dimming film including two dimming layers can be driven by a single power supply circuit (driver). Furthermore, it can be adapted to either common DC drive or common inversion drive. [Examples]
[0084] The present invention will be specifically described below with reference to examples, but the present invention is not limited in any way to these examples. The measurement methods for each characteristic are as follows. Unless otherwise specified, "parts" and "%" in the examples and comparative examples are based on weight.
[0085] <thickness> The measurement was performed using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). <Volume-average particle diameter of liquid crystal particles in liquid crystal emulsion> A sample was prepared by adding a few drops of liquid crystal emulsion to 100 mL of water. The sample was placed in the measurement holder of a laser diffraction particle size distribution analyzer (Microtrac, model name "MT3300EXII"), and measurement was performed after confirming that the concentration was measurable on the instrument's monitor. <Average particle size of resin particles> A sample was prepared by adding a few drops of resin dispersion to 100 mL of water. The sample was placed in the measurement holder of a dynamic light scattering particle size distribution analyzer (Microtrac, name "Nanotrac150"), and measurement was performed after confirming that the concentration was measurable on the instrument's monitor. <Hayes> The measurement was performed using a haze meter (manufactured by Nippon Denshoku Co., Ltd., product name "NDH4000") in accordance with JIS K 7136. <Total light transmittance> The measurement was performed using a haze meter (manufactured by Nippon Denshoku Co., Ltd., product name "NDH4000") in accordance with JIS K 7361. <Birefringence of liquid crystal components> The values disclosed by the liquid crystal component manufacturers were used.
[0086] [Example 1] (First and second transparent conductive films) A transparent conductive film having a [transparent substrate / transparent electrode layer] structure was obtained by forming an ITO layer (thickness: approximately 20 nm) on one side of a PET substrate (thickness: 50 μm) using a sputtering method. (Middle class) A PET substrate (manufactured by Panac Co., Ltd., product name "Panapiel") that had undergone a release treatment was used as a temporary support, and a resin layer was formed on the temporary support by the method described below. As binder resins, urethane-based polyfunctional acrylate A (DIC Corporation, trade name "UNIDIC ELS888") and urethane-based polyfunctional acrylate B (DIC Corporation, trade name "UNIDIC RS28-605") were used. These were mixed in a weight ratio of 8:2 for urethane-based polyfunctional acrylate A and 8:2 for urethane-based polyfunctional acrylate B, and diluted with ethyl acetate to prepare a coating composition. Using a gravure coater, the coating composition was applied to the peeled surface of the temporary support to a dry thickness of 1 μm, and then the coated layer was heated at 80°C. Next, a high-pressure mercury lamp was used to heat the coating at an integrated light intensity of 250 mJ / cm². 2 By irradiating with ultraviolet light, a laminate having a [temporary support / resin layer] structure was obtained. An ITO layer (thickness: approximately 20 nm) was formed on the surface of the resin layer of the above laminate by sputtering to obtain a laminate A having the configuration of [temporary support / resin layer / intermediate transparent electrode layer]. (Preparation of emulsion coating solution) A liquid crystal emulsion was prepared by mixing 42.3 parts of a liquid crystal component containing two or more liquid crystal compounds (JNC Corporation, product name "JC-5240XX", birefringence Δn=0.252 (ne=1.766, no=1.514), 0.7 parts of a dichroic dye (Nagase Vita Corporation, product name "NKX-3739"), 1.6 parts of a dichroic dye (Nagase Vita Corporation, product name "NKX-3708"), 55 parts of pure water, and 0.4 parts of a dispersant (Sanyo Chemical Industries, Ltd., "Newpol PE108") and treating the mixture with a high-pressure homogenizer. The average particle size of the liquid crystal particles in the obtained liquid crystal emulsion was 800 nm. An emulsion coating solution (solid content concentration: 35 wt%) was obtained by mixing 43 parts of the above liquid crystal emulsion, 35 parts of a polyether-based polyurethane resin aqueous dispersion (Covestro, product name "NeoRezR967", average polymer particle size: 80 nm, CV value = 0.27, solid content: 40 wt%), 0.4 parts of a leveling agent (DIC, product name "F-444"), 1 part of a crosslinking agent (tris[3-(2-methylaziridin-1-yl)propionic acid]=propyridinetrimethyl) and 20.6 parts of pure water.
[0087] (Preparation of PDLC film) The above emulsion coating solution was applied to the ITO layer surface of the second transparent conductive film and dried at 40°C to form a second PDLC layer with a thickness of 6 μm. Subsequently, using a laminator, laminate A was laminated on top of the second PDLC layer with a lamination pressure of 0.4 MPa / m, so that the ITO layer faced the second PDLC layer. This resulted in a laminated film having the following configuration: [second transparent substrate / second transparent electrode layer / second PDLC layer / intermediate transparent electrode layer / resin layer / temporary support]. The above emulsion coating solution was applied to the ITO layer surface of the first transparent conductive film and dried at 40°C to form a first PDLC layer with a thickness of 6 μm. Next, a temporary support removed from the laminated film was laminated on top of it so that the resin layer faced the first PDLC layer. The lamination was performed using a laminator while applying a lamination pressure of 0.4 MPa / m. As a result, a PDLC film having the following configuration was obtained: [first transparent substrate / first transparent electrode layer / first PDLC layer / resin layer / intermediate transparent electrode layer / second PDLC layer / second transparent electrode layer / second transparent substrate].
[0088] (Driving the PDLC film) The PDLC film described above was cut in half at a predetermined position to expose the edges of the first transparent conductive layer, the second transparent conductive layer, and the intermediate transparent conductive layer. The exposed portions of each transparent electrode layer were used as electrodes, and various voltages were applied to each electrode to operate the PDLC. At this time, a voltage was applied between the first transparent conductive layer, the second transparent conductive layer, and the intermediate transparent conductive layer. Figures 7 and 8 show the haze and total light transmittance when voltages from no voltage applied (applied voltage: 0V) to 50V were applied.
[0089] [Comparative Example 1] (First and second transparent conductive films) A transparent conductive film similar to that used in Example 1 was employed. (Preparation of emulsion coating solution) The same emulsion coating solution as in Example 1 was used. (Preparation of PDLC film) The above emulsion coating solution was applied to the ITO layer surface of the first transparent conductive film and dried at 40°C to form a PDLC layer with a thickness of 12 μm. Subsequently, a second transparent conductive film was laminated on top of the PDLC layer using a laminator, applying a lamination pressure of 0.4 MPa / m, so that the ITO layer faced the PDLC layer. This resulted in a PDLC film having the configuration of [first transparent substrate / first transparent electrode layer / PDLC layer / second transparent electrode layer / second transparent substrate].
[0090] (Driving the PDLC film) Both sides of the PDLC film described above were half-cut at predetermined positions to expose the edges of the first transparent conductive layer and the second transparent conductive layer. The exposed portions of each transparent electrode layer were used as electrodes, and various voltages were applied to these electrodes to operate the PDLC. Figures 7 and 8 show the haze and total light transmittance when voltages from no voltage applied (applied voltage: 0V) to 50V were applied.
[0091] As shown in Figures 7 and 8, the PDLC film of the example could be driven at a lower driving voltage compared to the PDLC film of the comparative example. [Industrial applicability]
[0092] The dimming film of the present invention can be suitably applied to displays such as advertisements and information boards, smart windows, and the like. [Explanation of symbols]
[0093] 10 First transparent conductive film 20 First light control layer 30 Middle Class 34 Intermediate transparent electrode layer 40 Second light control layer 50 Second transparent conductive film 100A~C Dimmable Film
Claims
1. The device comprises a first transparent conductive film, a first light-adjusting layer, an intermediate layer, a second light-adjusting layer, and a second transparent conductive film in this order. The first dimming layer and the second dimming layer each contain a composite material of a liquid crystal component and a polymer component. The aforementioned intermediate layer includes an intermediate transparent electrode layer. Dimming film.
2. The light-adjusting film according to claim 1, wherein the intermediate layer further comprises a resin layer disposed on at least one side of the intermediate transparent electrode layer.
3. The light-adjusting film according to claim 2, wherein the thickness of the resin layer is 5 μm or less.
4. The light-adjusting film according to claim 1, wherein the thickness of the intermediate layer is 12 μm or less.
5. The light-adjusting film according to claim 1, wherein the sum of the thicknesses of the first light-adjusting layer and the second light-adjusting layer is 5 μm or more.
6. The light-adjusting film according to claim 1, wherein the thickness of the first light-adjusting layer and the second light-adjusting layer are each 50 μm or less.
7. A method for using the dimming film according to claim 1, comprising applying a voltage between the first transparent conductive film and the intermediate transparent electrode layer and between the second transparent conductive film and the intermediate transparent electrode layer.
Citation Information
Patent Citations
Light control material, light control film and method for manufacturing light control film
JP2002189123A